Parameters and Measures in Assessment of Motor Learning in Neurorehabilitation; A Systematic Review of the Literature - Shishov, Nataliya; Melzer, Itshak; Bar-Haim, Simona (Frontiers in Human Neuroscience, 2017)
Upper limb function, essential for daily life, is often impaired in individuals after stroke and cerebral palsy (CP). For an improved upper limb function, learning should occur, and therefore training with motor learning principles is included in many rehabilitation interventions. Despite accurate measurement being an important aspect for examination and optimization of treatment outcomes, there are no standard algorithms for outcome measures selection. Moreover, the ability of the chosen measures to identify learning is not well established. We aimed to review and categorize the parameters and measures utilized for identification of motor learning in stroke and CP populations. PubMed, Pedro and Web of Science databases were systematically searched between January 2000 and March 2016 for studies assessing a form of motor learning following upper extremity training using motor control measures. Thirty-two studies in persons after stroke and ten studies in CP of any methodological quality were included. Identified outcome measures were sorted into two categories, ‘parameters’, defined as identifying a form of learning, and ‘measures’, as tools measuring the parameter. Review’s results were organized as a narrative synthesis focusing on the outcome measures. The included studies were heterogeneous in their study designs, parameters and measures. Parameters included adaptation (n=6), anticipatory control (n=2), after-effects (n=3), de-adaptation (n=4), performance (n=24), acquisition (n=8), retention (n=8) and transfer (n=14). Despite motor learning theory's emphasis on long-lasting changes and generalization, the majority of studies did not assess the retention and transfer parameters. Underlying measures included kinematic analyses in terms of speed, geometry or both (n=39), dynamic metrics, measures of accuracy, consistency and coordination. There is no exclusivity of measures to a specific parameter. Many factors affect task performance and the ability to measure it – necessitating the use of several metrics to examine different features of movement and learning. Motor learning measures’ applicability to clinical setting can benefit from a treatment-focused approach, currently lacking. The complexity of motor learning results in various metrics, utilized to assess its occurrence, making it difficult to synthesize findings across studies. Further research is desirable for development of an outcome measures selection algorithm, while considering the quality of such measurements.